Relationship between myopia and diagnosis rates of dry eye disease and related indicators: a systematic review and meta-analysis - Kai Wu; Kai Wu; Yunfeng Yu; Jian Shi; Huimei Chen; Huimei Chen; Canming Xie; Canming Xie; Yu Tang; Yu Tang; Xiaolei Yao; Xiaolei Yao (Frontiers in Medicine)
BackgroundThe association between myopia and dry eye disease (DED) has recently garnered considerable attention. This study aimed to compare the diagnosis rates of DED and its indicators between myopic and emmetropic patients to elucidate the association between myopia and DED.MethodsWe retrieved relevant literature published through November 2024 from English databases, such as PubMed, Embase, the Cochrane Library, and Web of Science, as well as Chinese databases, such as the China National Knowledge Infrastructure, WanFang, VIP, and SinoMed. The studies were then screened for inclusion and exclusion criteria, and the basic information and outcome data of the included studies were recorded. The methodological quality of the included studies was assessed by the Joanna Briggs Institute. Finally, RevMan 5.3 was used to perform meta-, subgroup, and sensitivity analyses, as well as a publication bias assessment of the outcome data.ResultsThis study included 8 studies with a sample size of 14,232 patients. The meta-analysis showed that compared with emmetropic eyes, the diagnostic rate of DED in myopic eyes increased significantly, by 104% [odds ratio (OR) = 2.04, 95% confidence interval (CI) = 1.39–2.99, P = 0.0002, I2 = 91%], while the tear break-up time (BUT) was reduced significantly, by 6.31 s [weighted mean difference (WMD) = −6.31, 95% CI = −7.32 to −5.29, P < 0.00001, I2 = 0%]. However, there was no significant difference in the rate of positive corneal staining (OR = 2.53, 95% CI = 0.22–29.07, P = 0.46, I2 = 68%). Funnel plots showed a potential publication bias in DED diagnosis rate, rate of positive corneal staining, and BUT. An evaluation showed that the evidence quality of DED diagnosis rate, BUT and rate of positive corneal staining were extremely low.ConclusionThere were significant differences in the DED diagnosis rate and BUT between myopic and emmetropic patients, suggesting that myopia may be a potential risk factor for DED. The regular screening for DED should be a focus in myopic populations to improve detection and diagnosis rates.Systematic review registrationCRD42024611482, https://www.crd.york.ac.uk/PROSPERO/myprospero